One-loop formulas for off-shell decay \(H^* → W^+W^-\) in 't Hooft-Veltman gauge and its applications - Phan, Khiem Hong; Tran, Dung Tri; Nguyen, Anh Thu (Communications in Physics, 2023)
We present analytic results for one-loop radiative corrections to off-shell decay \(H^* → W^+W^-\) in 't Hooft-Veltman gauge within the Standard Model framework. In numerical results, we show off-shell decay rate and its corrections with varying off-shell Higgs mass. The results show that the corrections are of 10% contributions to the total decay rates. Furthermore, we study the impacts of one-loop radiative corrections to the off-shell decay \(H^* → W^+W^-\) in Higgs processes at future colliders. The signal processes such as \(e^-e^+→ ZH^*→ Z(WW)\) with including the initial beam polarizations and \(e^-e^+→ u_e\bar{ u}_e H^* → u_e\bar{ u}_e (WW)\) and \(e^-γ → e^-H^* → e^-WW\) are examined. We find that the effects are visible impacts and these should be taken into account at future colliders.